Effects of Heat Input on Microstructure, Corrosion and Mechanical Characteristics of Welded Austenitic and Duplex Stainless Steels: A Review - Mohammed, Ghusoon R.; M., Ishak; S. N., Aqida; Hassan, A. Abdulhadi (MDPI AG, 2017)
The effects of input heat of different welding processes on the microstructure, corrosion, and mechanical characteristics of welded duplex stainless steel (DSS) are reviewed. Austenitic stainless steel (ASS) is welded using low-heat inputs. However, owing to differences in the physical metallurgy between ASS and DSS, low-heat inputs should be avoided for DSS. This review highlights the differences in solidification mode and transformation characteristics between ASS and DSS with regard to the heat input in welding processes. Specifically, many studies about the effects of heat energy input in welding process on the pitting corrosion, intergranular stress, stress-corrosion cracking, and mechanical properties of weldments of DSS are reviewed.